Genotype x environment effects on severity of cassava bacterial blight disease caused by Xanthomonas axonopodis pv. manihotis - Dixon, A.; Ngeve, J.; Nukenine, E. (Springer, 2002)
Nine cassava genotypes were grown for three years at six sites representing three agro-ecological zones in Nigeria to study their reaction to cassava bacterial blight (CBB), investigate genotype × environment (G×E) interaction patterns for their reaction to CBB, and to identify genotypes with stability to the disease, using the additive main effects and multiplicative interaction (AMMI) statistical model. Environments, genotypes and G×E interactions accounted for71.8%, 12.0% and 16.2% of the treatment sums of squares (SS), and were highly significant (P<0.0001) for the disease, indicating that genotypes responded differentially to CBB infection across environments. Clones 30555,91934, U/41044, and 4(2)1425 showed the least CBB disease ratings. Other clones showed erratic and fluctuating reactions to CBB from environment to environment and were thus considered unstable to the disease. CBB was most severe in 1989 (with a mean score of 2.46) and least so in 1990 (with a score of 2.06). The sites with the most disease were Ibadan, Ilorin and Ubiaja (1989), Ibadan and Ubiaja (1990) and Mokwa (1991). Because of the favourable conditions for disease development at those sites, they could be appropriate for screening cassava genotypes for CBB resistance. The AMMI model selected AMMI1 as the best predictor for CBB because it had the smallest actual root mean square prediction difference (0.37646), and explained 90.7% of the G×E interaction for CBB. The AMMI model was successful in selecting the genotypes 30555, U/41044 and 4(2)1425 and the environments Ibadan 1989, Ilorin 1989 and Onne 1990 with stability of reaction to the disease.